CoFe2O4 Nanocrystals Mediated Crystallization Strategy for Magnetic Functioned ZSM‐5 Catalysts. (22nd June 2018) - Li, Bin; Yildirim, Erol; Li, Wei; Qi, Dianpeng; Yu, Jiancan; Wei, Jiaqi; Liu, Zhiyuan; Sun, Zhenkun; Liu, Yong; Kong, Biao; Xue, Zhaoteng; Liu, Zhuangjian; et al.
Abstract: Zeolites have many applications in the petrochemical and fine chemical industry and their functionalization does expand the spectrum of potentials. However, the integration of functional nanocrystals into zeolite frameworks with controlled size, dispersion, and crystallization behavior still remains a significant challenge. Here, a new synthesis of magnetic functioned ZSM‐5 zeolite catalysts via a CoFe2 O4 nanocrystal mediated crystallization strategy is reported. It is found that high crystallinity of CoFe2 O4 nanocrystals results in a well‐dispersed encapsulation of them into a single‐crystal of ZSM‐5 due to non‐further‐grown nanocrystals during the fast ZSM‐5 growth. On the contrary, low crystallinity of CoFe2 O4 nanocrystals leads to the polycrystalline zeolite growth due to the secondary growth of nanocrystals accompanied by the zeolite crystallization and large lattice mismatch between them. The successful encapsulation of small CoFe2 O4 nanocrystals (≈4 nm) into single crystals lies on the preattachment of them into solid silica gel. During the growth of ZSM‐5 crystals, no secondary growth of nanocrystals happens and its motion is restricted. The encapsulation of magnetic CoFe2 O4 nanocrystals not only endows magnetic function into zeolites for the first time, but also does not impact catalytic performance of ZSM‐5 in acetalization of cyclohexanone with methanol, which is highly promising in catalytic industries. Abstract : Guest CoFe2 O4 nanocrystals with different relative crystallinity lead to different host ZSM‐5 crystallization behavior. Nanocrystals with high crystallinity lead to a successful encapsulation into the zeolite single crystal. Low crystallinity nanocrystals composed of ions, amorphous, and crystalline result in polycrystalline ZSM‐5 growth.